2012
DOI: 10.1039/c2jm31541f
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to improve the gas storage capacity of ZIF-8

Abstract: In this work a novel method for enhancing the gas storage capacity of metal-organic frameworks (MOFs), i.e. saturating the MOF with a suitable quantity of water and forming hydrates in it, was proposed. Commercialized ZIF-8 was adopted as it is very stable under an atmosphere of water. The adsorption and hydrate formation behaviors of methane in wet ZIF-8 with five different water contents (0.0%, 16.3%, 27.7%, 30.6%, and 35.1%, mass percentages) were investigated under hydrate formation conditions and the stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(105 citation statements)
references
References 35 publications
5
100
0
Order By: Relevance
“…On the contrary, hydrophobic MOFs promote methane hydrate formation, although the hydrate growth takes place in the external surface or in the interparticle space (see Figure ). These systems where water is excluded from the inner cavities (for instance ZIF‐8) can be used as a dual system with methane physisorption in the inner empty cavities and methane hydrate formation in the interparticle space, the extend of hydrate formation being tailored by the amount of water incorporated ,…”
Section: Methane Hydrate In Confined Spacesmentioning
confidence: 99%
“…On the contrary, hydrophobic MOFs promote methane hydrate formation, although the hydrate growth takes place in the external surface or in the interparticle space (see Figure ). These systems where water is excluded from the inner cavities (for instance ZIF‐8) can be used as a dual system with methane physisorption in the inner empty cavities and methane hydrate formation in the interparticle space, the extend of hydrate formation being tailored by the amount of water incorporated ,…”
Section: Methane Hydrate In Confined Spacesmentioning
confidence: 99%
“…Specifically, Mu et al reported that the methane storage capacity of one kind of MOF (ZIF-8) can be increased to 45% with the formation of methane hydrate in the ZIF-8. 38 Such a significant increase in gas sorption raises the possibility of two contributions: the inclusion of gas in the gas hydrates' water cages and the inclusion of gas in the intrinsic micropores of MOFs. These two different mechanisms for molecular capture might indicate a new strategy for gas storage and separation, which could lead to more complex patterns from mutual interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the adsorption amounts of C 2 H 4 and CH 4 shows great promise for their separation. In addition, Mu et al 11 measured the adsorption and hydration behavior of CH 4 in wet ZIF-8 with five different water contents under hydrate formation conditions, and the overall storage …”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%